Images of the Nation : Different Meanings of Dutchness, 1870-1940 - Galema, A.,; Henkes, B.,; Velde, H. te, (Amsterdam Studies on Cultural Identity ;, 1993)
This collection of case studies investigates the significance and function of national identity. The authors see national consciousness in terms of the circumstances in which it arose, and in terms of the meaning which it had for a specific group or individual. Representations of the nation could serve to legitimize or support specific political or social agendas, or to provide people with a point of fixity amidst changing circumstances. The articles in this volume trace these aspects of national consciousness in the case of a single country: The Netherlands.